Cross-Border Cooperation on Security in Europe - Bogacka, Emilia (Quaestiones Geographicae, 2010)
The aim of the article is to present cross-border cooperation on security. For this purpose, various problems in the European Union with respect to criminal policy must be described. The article consists of three parts. The first presents selected European institutions established to prevent and fight crime. The second concentrates on the control of external EU borders, quoting people's opinions on this matter and describing one of the EU programmes, the European Neighbourhood & Partnership Instrument: Cross-Border Cooperation. The third part focuses on security of the Polish borders as those which in recent years have witnessed serious political changes - Poland's accession to the European Union and the Schengen zone. The paper finishes with conclusions.